Information technologies and the evolution of the digital divide in Mexico: a public policy approach - Humberto Merritt (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2011)
The rapid diffusion of Information Technologies (ITs) has noticeably influenced the ability of societies to stimulate economic growth and development. Among these technologies, the Internet stands out due to its contribution to the advancement of education, learning and knowledge. Hence, the commitment of some developing nations like Mexico to the diffusion of the Internet has become a top issue in their policy agendas. However, the country's promotion of this technology has undergone a number of setbacks, mainly due to a misinterpretation of the factors causing the so-called 'digital divide'. Hence, the purpose of this paper is to analyze the rationale for governmental intervention regarding the diffusion of the Internet in Mexico.